The cult of King Charles the martyr - Lacey, Andrew, 1960- (Boydell Press, 2003)
The first study to deal exclusively with the cult ofKing Charles the Martyr - Charles I as suffering, innocent king, walking in the footsteps of his Saviour to his own Calvary at Whitehall - and the political theology underpinning it, taking the story up to 1859.
Keywords: Charles -- I, -- King of England, -- 1600-1649 -- Cult.; Church of England. -- Book of common prayer.; Charles -- I, -- King of England, -- 1600-1649; Book of common prayer (Church of England); Christian martyrs -- Great Britain -- Biography.; Christian saints -- Great Britain -- Biography.; Great Britain -- Kings and rulers -- Biography.; Martyrs chrétiens -- Grande-Bretagne -- Biographies.; RELIGION -- Christianity -- Anglican.; HISTORY -- Modern -- General.; Christian martyrs; Christian saints; Cults; Kings and rulers; Great Britain; Biographies; Biographies.